Resilience and challenges of peritoneal dialysis survivors in the aftermath of the 2023 Kahramanmaraş earthquake - TUĞCU, MURAT; TUĞLULAR, ZÜBEYDE SERHAN (My University, 2024)
Introduction: Peritoneal dialysis (PD) remains understudied in disaster nephrology. This retrospective multicenter study explores the experiences of PD survivors following the February 6, 2023, Kahramanmaraş Earthquake. Methods: Adult PD patients from 11 affected cities were analyzed to assess challenges faced during and postearthquake, alongside clinical outcomes. Results: Among 101 participants (median age: 45 years, median PD duration: 24 months), 57 were female, with 79 on continuous ambulatory PD. Challenges included power outages and water shortages, with primary shelter in kin\"s houses (33%) and homes (28%). Twelve patients experienced PD program delays, and three lacked assistance postdisaster. Sixteen patients changed PD modalities, with seven experiencing postearthquake peritonitis. Clinical parameters remained stable, except for a slight decrease in hemoglobin levels. Conclusion: Despite challenges, PD survivors exhibited resilience, highlighting the importance of addressing peritonitis and unusual pathogens in disaster preparedness initiatives.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Hematoloji; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Hematology; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; HEMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; HEMATOLOGY; disaster; disaster nephrology; earthquake; peritoneal dialysis; peritonitis